Pengaruh Website Quality, Word of Mouth, dan Harga Terhadap Keputusan Pembelian Smartphone Vivo di Kota Palembang - Al-Azhar, Muhammad Yudha; Asiati, Diah Isnaini; Astuti, Maidiana (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This research aims to determine the influence of website quality, word of mouth, and price on the purchase decision of Vivo smartphones in Palembang City, to determine the influence of website quality on the purchase decision of Vivo smartphones in Palembang City, to determine the influence of word of mouth on the purchase decision of Vivo smartphones in Palembang City, and to determine the influence of price on the purchase decision of Vivo smartphones in Palembang City. The type of this research is associative research. The variables used in this study are website quality, word of mouth, and price as independent variables, and purchase decision as the dependent variable. The research population is finite with a sample size of 100 respondents who are users of Vivo smartphones. The data used is primary data, with the data collection technique in the research being the distribution of questionnaires. The data analysis used in this study is multiple linear regression analysis. The research results show that there is a positive and significant influence of website quality, word of mouth, and price on the purchasing decision of Vivo smartphones in the city of Palembang. There is a positive and significant influence of website quality on the purchasing decision of Vivo smartphones in the city of Palembang. There is a positive and significant influence of word of mouth on the purchasing decision of Vivo smartphones in the city of Palembang, and there is a positive and significant influence of price on the purchasing decision of Vivo smartphones in the city of Palembang.